The poetics and politics of the desert : landscape and the construction of America - Gersdorf, Catrin (Spatial practices, 2009)
This study explores the ways in which the desert, as topographical space and cultural presence, shaped and reshaped concepts and images of America. Once a territory outside the geopolitical and cultural borders of the United States, the deserts of the West and Southwest have since emerged as canonical American landscapes. Drawing on the critical concepts of American studies and on questions and problems raised in recent debates on ecocriticism, The Poetics and Politics of the Desert investigates the spatial rhetoric of America as it developed in view of arid landscapes since the mid-nineteenth.